Games, Rhymes, and Wordplay of London Children - Kelsey, N. G. N. (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book presents a unique annotated collection of some 2000 playground games, rhymes, and wordplay of London children. It charts continuity and development in childlore at a time of major social and cultural change and offers a detailed snapshot of changes in the traditions and language of young people. Topics include: starting a game; counting-out rhymes; games (without songs); singing and chanting games; clapping, skipping, and ball bouncing games; school rhymes and parodies; teasing and taunting; traditional belief and practice; traditional wordplay; and a concluding miscellany. Recorded mainly in the 1980s by primary schoolteacher Nigel Kelsey, transcribed verbatim from the children's own words, and accompanied by extensive commentaries and annotation, the book sets a wealth of new information in the wider historical and contemporary context of existing studies in Britain, Ireland, and other parts of the English-speaking world. This valuable new resource will open new avenues for research and be of particular interest to folklorists and linguists, as well as to those working across the full spectrum of social, cultural, and educational studies. N. G. N. Kelsey worked as a primary school teacher in London from 1952 until his retirement in 1982. During this time, he collected examples of the language and lore of the children under his care. Janet E. Alton is an independent researcher based at the Centre for English Traditional Heritage, UK. J. D. A. Widdowson is Director of the Centre for English Traditional Heritage, UK.